Perceived fairness and marital satisfaction: The role of the presence of children with disabilities - Klarinthia Ratri; Yudiana Ratnasari (HUMANITAS published by Universitas Ahmad Dahlan., 2023)
Perceived fairness has been consistently found to have a significant positive correlation with marital satisfaction. Furthermore, numerous studies on perceived fairness have been conducted related to parents of children with disabilities, considering the difficulties encountered by these parents due to their children’s specialized needs and demands. As a result, these challenges usually affect their marital relationship more than the other couples. Therefore, this study aimed to examine the relationship between perceived fairness and marital satisfaction moderated by the presence of children with disabilities. The Indonesian version of the Perceived Fairness instrument and Quality of Marriage Index were used to measure perceived fairness and marital satisfaction in 335 married Indonesian participants, including both parents of children with and without disabilities. Data analysis was performed using Hayes PROCESS. The result showed that perceived fairness was significantly correlated to marital satisfaction in both parents of children with and without disabilities. However, no significant interaction was found by the presence of children with disabilities on the relationship between perceived fairness and marital satisfaction. The results of this study provide a strong implication for mental health practitioners regarding the intervention goals for families and parents of children with disabilities.